Using Linear Local Dependence Measure to Study the factors that are Leading to the Growth of Preferring the Application in Private Universities of Iraq - N. Abdulahad, Fedaa; Z. Ahmood, Ranen (Iraqi Journal of Science, 2023)
In this paper a measure of linear local dependence has been used between tworandom variables and a study is conducted for the properties of this measure wheretwo examples of bivariate probability distributions has been considered, which arebivariate Gumbel distribution and bivariate Beta-Stacy distribution, and applied ondata collected by using a questionnaire conducted to study the reasons for theincrease of application in private collages in Iraq. Five elements has been consideredas random variables and the dependence has been measured between every twoelements to estimate how correlated these elements are and their effect on theapplication in private collages of Iraq generally and Baghdad specifically.